Collaboration Skills of Phase F High School Students through the Use of Physics Electronic Modules Based on Project Based Learning Integrated with Local Wisdom Maelo Pukek - Dewi Juita; Feny Irawani (Postgraduate, University of Mataram, 2025)
This research was motivated by the low collaboration skills of high school students in phase F. This was due to a lack of teaching materials that were suitable for the characteristics of physics learning, which emphasizes direct experience for students, and that were suitable for the characteristics of the students being taught. Modules are very suitable for use in the learning process because they can be adapted to student characteristics and needs. Electronic modules based on project-based learning (PjBL) are able to provide direct experiences to students. The integration of electronic PjBL modules with local maelo pukek wisdom, which is closely related to students' lives, is very appropriate for collaboration. Students create miniatures of maelo pukek with their peers by incorporating physics concepts into them, which can develop students' collaboration skills. The physics concept that supports the process of making this net is the concept of fluid dynamics. This study was conducted to determine the level of students' collaborative skills through the use of electronic modules. The research approach used was quantitative with a pre-experimental method. The results showed that students' collaborative skills were quite good, with an average score of 75.00 in the use of project-based electronic modules integrated with local wisdom related to maelo pukek. The ability to provide feedback and discuss with peers is the best indicator of collaborative skills.